Exploring the role of context on the existing evidence for reconsolidation of episodic memory (2019)
Recent research has provided evidence for memory modifications when a post-reactivation treatment (e.g., drugs, new learning) interferes with the memory re-stabilisation (reconsolidation) process. This finding contradicts the long-standing consolidation theory and has high practical and theoretical implications. With an object-learning paradigm, it was shown that episodic memory is highly susceptible to interfering material presented after its reactivation [Hupbach, A., Gomez, R., Hardt, O., and Nadel, L. (2007). Reconsolidation of episodic memories: A subtle reminder triggers integration of new information. Learning and Memory, 14, 47–53. doi:10.1101/lm.365707]. The reactivation of a learned list (List 1) before a second learned list (List 2) led to intrusion errors from List 2 when trying to recall List 1, but not vice-versa. Their work has been widely cited and their findings have been explained according to reconsolidation theory. For the first time, we systematically explored the role of retrieval context as an alternative explanation for Hupbach’s results. Our results showed that the intrusion effect occurs independently of the retrieval context (Experiment 1). Additionally, even when the intrusion rate probability is increased (i.e., List 1 memory test is performed in the List 2 learning context), the groups that did not reactivate the original list did not commit intrusion errors (Experiment 2). In sum, we found that the intrusion effect critically depends on the presence of reactivation, discarding alternative interpretations of the results. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.